IMPLEMENTASI APLIKASI CLOUD DESIGN UNTUK PEMBELAJARAN SISWA DI SMK NEGERI 10 DAN 18 SAMARINDA (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
This study aims to develop, determine the feasibility of android-based learning media. This type of research uses research and development (Research and Development) methods with the Borg & Gall development model consisting of 5 main stages which include: a) conducting preliminary research, b) developing the initial product with Kodular Creator, c) conducting product validation, d ) conducting trials, and e) making the final product. Data collection techniques used are questionnaires and interviews Keywords: Borg & Gall, Android-Based Learning Media, Informatics